Heterogeneous Cross-Domain Identity Authentication Scheme Based on Proxy Resignature in Cloud Environment. (17th November 2020) - Lv, Yongyang; Liu, Wenju; Wang, Ze
Abstract : Based on proxy resignature, the signature transformation between trust domains of different cryptographic systems is realized with the help of the cloud authentication center, so as to achieve cross-domain access between users and cloud service providers in heterogeneous environment. Hierarchical ID tree realizes the uniqueness of identity in communication, and the security of heterogeneous cross-domain identity authentication is enhanced by the two-factor authentication of "password + key" and temporary identity replacing real identity. The security of the scheme is proved under the CK model, which can anonymously trace entity identity, resist replay attacks, replacement attacks, and man-in-the-middle attacks, and the simulation experiment is carried out. By searching it in related fields, no paper on heterogeneous cross-domain identity authentication based on proxy resignature has been published yet. The results of this paper show that the proposed scheme has better computing performance and higher security.